2019
DOI: 10.18203/2349-3291.ijcp20190677
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary tract infection in febrile preschool children

Abstract: Background: Children with fever is a common and comprise a substantial proportion of the practice in outpatient department and emergency department. Little attention has been focused on the identification of urinary tract infection (UTI) in febrile in infants and children in the emergency department, despite recent information that suggests a high prevalence of urinary tract infections and significant associated morbidity in these patients. The present study is undertaken to estimate the prevalence of urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Where, Zα = 1.96 at 95% confidence interval, p = prevalence of event of interest = 6.36% as per previous research [ 12 ], L = absolute error around the reported prevalence. Here it is assumed to be 5 (absolute).…”
Section: Methodsmentioning
confidence: 99%
“…Where, Zα = 1.96 at 95% confidence interval, p = prevalence of event of interest = 6.36% as per previous research [ 12 ], L = absolute error around the reported prevalence. Here it is assumed to be 5 (absolute).…”
Section: Methodsmentioning
confidence: 99%